Waiting for... the Debutant Director - CIOBOTARI, Călin (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
The present study aims to discuss a series of problems identified over time in Romanian directing education, with an emphasis on the Theatre Faculty of Iași where the author has been teaching for many years. In the second part of the paper, I publish the results of a questionnaire that I did, on the occasion of this research, among the best graduates of the last five years of the Department of Directing at the Faculty of Theatre Iasi.